Antonymy and networking lexical organization in the 1st CEB: teaching proposal using bimodal narratives and increased reality (2019)
In this paper, it will be presented a didactic proposal for teaching word multiple relationships, in primary school, including Augmented Reality tools. It is proposed that semantic relations learning is not based on antonymic binary relations, which would promote a dichotomous thought in children. Through three bimodal narratives, possibilities of lexical organization were questioned, placing apparent dichotomous pairs of words in contexts of occurrence that may admit gradation or synonymy as semantic relations, thus compromising the inevitability of binary antonymic organization/interpretation, but also the negatives consequences of such kind of teaching to early age children.